Resting and exercise metabolic characteristics in obese children with insulin resistance - Youxiang, Cao; Lin, Zhu; Zekai, Chen; Weijun, Xie (Frontiers in Physiology, 2022)
Purpose: This study aimed to explore the characteristics of resting energy expenditure (REE) and lipid metabolism during incremental load exercise in obese children and adolescents with insulin resistance (IR) to provide evidence for exercise intervention in obese children and adolescents with IR. Method: From July 2019 to August 2021, 195 obese children and adolescents aged 13–17 were recruited through a summer camp. The participants were divided into IR (n = 67) and no-IR (without insulin resistance, n = 128) groups and underwent morphology, blood indicators, body composition, and resting energy consumption gas metabolism tests. Thirty participants each were randomly selected from the IR and no-IR groups to carry out the incremental treadmill test. Results: Significant metabolic differences in resting and exercise duration were found between the IR and no-IR groups. In the resting state, the resting metabolic equivalents (4.33±0.94 mL/min/kg vs. 3.91 ± 0.73 mL/min/kg, P = 0.001) and REE (2464.03 ± 462.29 kcal/d vs. 2143.88 ± 380.07 kcal/d, P＜0.001) in the IR group were significantly higher than in the no-IR group. During exercise, the absolute maximal fat oxidation (0.33 ± 0.07 g/min vs. 0.36 ± 0.09 g/min, P = 0.002) in the IR group was significantly lower than in the no-IR group; maximal fat oxidation intensity (130.9 ± 8.9 bpm vs. 139.9 ± 7.4 bpm, P = 0.040) was significantly lower in the IR group. Conclusions: Significant resting and exercise metabolic differences were found between obese IR and no-IR children and adolescents. Obese IR children and adolescents have higher REE and lower maximal fat oxidation intensity than obese no-IR children and adolescents.